Removal of BTX from aqueous solutions by adsorption using PDMS foam - Alatawi, Lila; Abdullah, Abdul Halim; Md Jamil, Siti Nurul Ain; Yunus, Robiah (National Information and Documentation Centre, 2025)
Due to untreated wastewater disposal from a growing population and industry, biological and chemical pollutants have accumulated in the environment. Benzene, toluene, and xylene (BTX) are among the most frequently encountered contaminants in industrial wastewater. Due to their toxic and carcinogenic nature, BTX-containing industrial wastewater requires proper treatment prior to discharge to open water. This study examined the monocomponent adsorption of BTX from an aqueous solution using polydimethylsiloxane (PDMS) foam. Adsorption performance was optimised under various experimental conditions, including the effects of contact time, adsorption dosage, and initial concentration. The adsorption capacity of PDMS foam followed the order X > T > B, and the equilibrium of adsorption was reached in 6 h. The adsorption isotherms were analysed using the Langmuir, Freundlich, and Temkin models to evaluate their suitability for fitting the experimental data. The kinetics of the process were assessed employing both the pseudo-first-order and pseudo-second-order models. The adsorption data exhibited a good fit with Freundlich isotherms and a pseudo-second-order kinetic model. Based on experimental findings, PDMS foam shows great promise as an effective adsorbent for removing BTX from water.